The Influence of Financial Literacy on Financial Management in Small & Medium Enterprises (Case Study on Coffee Shop Management in Bandung City Period 2020 – 2021) - Novariani, Rifa Keisha; Dialysa, Fia (STIE Ekuitas, 2024)
Introduction/Main Objectives: This study aims to determine how the development of financial literacy and management as well as to determine the effect of financial literacy on basic financial knowledge, savings and credit, investment and insurance on financial management at SMEs in the form of Coffee Shop in Bandung City. Background Problems: Financial literacy is a person's understanding or ability to measure financial concepts and has the ability to manage finances well. Financial literacy is very necessary for SMEs in managing their business finances. Research Methods: The method used is descriptive and verification analysis method with a quantitative approach. The technique of determining the sample using Nonprobability Sampling. Finding/Results: The results of the study found that literacy about basic financial knowledge has a significant effect on SME’s financial management, literacy about savings and credit has a significant effect on SME’s financial management, literacy about Investment has a significant effect on SME’s financial management and literacy about insurance also has a significant effect on SME’s financial management. Conclusion: The more literate on financial knowledge, savings and credit, investment and insurance, the more SME’s financial management increase.